Advanced technologies for reducing greenhouse gas emissions from rice fields: Is hybrid rice the game changer? - Khatibi, Seyed Mahdi Hosseiniyan; Adviento-Borbe, Maria Arlene; Dimaano, Niña Gracel; Radanielson, Ando M.; Ali, Jauhar (Elsevier BV, 2025)
Rice is a staple food for half of the world’s population and the largest source of greenhouse gas (GHG) from the agricultural sector, responsible for approximately 48% of GHG emissions from croplands. With the rapid growth of the human population, the increasing pressure on rice systems for extensive and intensive farming is associated with an increase in GHG emissions that is impeding global efforts to mitigate climate change. The complex rice environment, with its genotypic variability among rice cultivars, as well as emerging farming practices and global climatic changes, are important challenges for research and development initiatives that aim to lower GHG emissions and increase crop productivity. A combination of approaches will likely be needed to effectively improve the resilience of modern rice farming. These will include a better understanding of the major drivers of emissions, different cropping practices to control the magnitude of emissions, and high yield performance through systems-level studies. The use of rice hybrids may give farmers an additive advantage, as hybrids may be better able to resist environmental stress than inbred varieties. Recent progress in the development and dissemination of hybrid rice has demonstrated a shift in the carbon footprint of rice production and is likely to lead the way in transforming rice systems to reduce GHG emissions. The application of innovative technologies such as high-throughput sequencing, gene editing, and AI can accelerate our understanding of the underlying mechanisms and critical drivers of GHG emissions from rice fields. We highlight advanced practical approaches to rice breeding and production that can support the increasing contribution of hybrid rice to global food and nutritional security while ensuring a sustainable and healthy planet.